An Analysis of Code-Mixing Used by Agnez Monica in A Video Podcast on Deddy Corbuziers Youtube Channel - I Gede Satyadhi Satvika (STKIP AGAMA HINDU SINGARAJA, 2023)
In communicating and interacting with each other we need to use language. Some society can be bilingual and some other can be multilingual. By conducting a conversation or monologue using two or more languages, sociolinguistic scientists call it code-switching and code-mixing. This study focuses more on analyzing the type and level of code-mixing carried out by Agnez Monica in the video podcast on Deddy Corbuzier's YouTube channel. This research aims to make people understand the purpose and use of code-mixing itself and reduce misunderstandings about using code-mixing in communication. This research was conducted to determine the types and to describe the level of code-mixing code-mixing used by Agnez Monica in the video podcast of Deddy Corbuzier's YouTube channel. The type of code-mixing used in analyzing video podcasts uses Muysken's theory, including insertion, substitution, and congruent lexicalization. The level of code-mixing used in analyzing video podcasts uses Suwito's theory, including word level, phrase level, idiom level, baster level, repetition rate, and clause level.